Cryptanalysis of columnar transposition cipher with long keys. Issue 4 (3rd July 2016) - Lasry, George; Kopal, Nils; Wacker, Arno
ABSTRACT: The classical columnar transposition cipher was the most popular type of transposition cipher. It was in use mainly during the second half of the nineteenth century and the first half of the twentieth century. It also served as a building block for more complex ciphers, such as the ADFGVX cipher and the double transposition cipher. Pen-and-paper as well as computerized methods for the cryptanalysis of the columnar transposition cipher have been published, but those apply mainly to the easier cases of short keys and complete transposition rectangles. In this article, a novel approach for the cryptanalysis of the columnar transposition cipher (when used with long keys) is presented. It is based on a two-phase hill climbing algorithm, a two-dimensional fitness score, and special transformations on key segments. This ciphertext-only method allows for the recovery of transposition keys with up to 1, 000 elements, and up to 120 elements for worst case transposition rectangles.